Gender and Modality Effects on EFL Speaking Anxiety: A Study of Online and Traditional Classrooms at UIN Alauddin Makassar - Asnur, Sardian Maharani; Nagauleng, Andi Mukarramah; nahdhiyah, nahdhiyah; Waris, Ahmad Mustamir (STAIN Majene, 2025)
This study aims to examine how gender and learning modality (traditional vs. online class) influence speaking anxiety among fourth-semester students of the English Language and Literature Department. A total of sixty students, comprising 30 males and 30 females, participated in the study by completing a modified Foreign Language Classroom Anxiety Scale (FLCAS). The data were analyzed using descriptive statistics and independent-samples t-tests. The results show that speaking anxiety was consistently higher in the traditional classroom than in the online class across all FLCAS subscales, with significant differences favouring lower anxiety in online classes (p < .001). Gender differences were descriptive but not statistically significant in the traditional class, indicating that the high-pressure nature of face-to-face communication elevated anxiety similarly for both groups. In contrast, a significant gender difference emerged in the online class for the Fear of Negative Evaluation subscale (p = .033), with female students reporting stronger evaluative concern. Overall, the findings indicate that speaking anxiety is shaped more by learning modality than by gender, and that online settings may reduce certain anxiety triggers for learners. However, the limited sample size calls for further studies with larger and more diverse populations to improve the generalizability of the findings